PEMBELAJARAN MELALUI LATIHAN AZAN UNTUK MENGEMBANGKAN KEPERCAYAAN DIRI DAN AFEKSI ANAK TERHADAP SIMBOL-SIMBOL ISLAM - Rahman; Zahriani JF, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of learning strategies through adhan practice in developing self-confidence and children’s affection toward islamic symbols at Tadika Ummi Bestari, Kota Damansara, Malaysia. This study emplys a descriptive qualitative approachwith a case study design, in wich the researcher is diretly involved and act as a trainer troughout the research process. Data were collected through observation, interviews, and documentation, and analyzed inductively. The findings show that structure adhan practice using modeling, imitation, habituation, gradual practice, and positive reinforcement encourages children’s courage, self-confidence, and positive emotional responses toward islamic symbols. Children actively participated and showed progressive improvement from group practice to individual performance. This study concludes that adhan practice can serve as an effective learning strategy to support affective and social development in early childhood education.